(untitled) (Sains Humanika, 2022)
The decline of student participation in science streams is an issue of concern and it is often discussed in many studies internationally. This study aims to refine the selection factors of chemistry majors among undergraduates based on gender, race, and academic achievement. The design of the study is quantitative, and the selection of the sample is purposive sampling. A set of questionnaires containing 47 items was distributed to 118 respondents from year one majoring in chemistry at one of the institutions of higher learning in Johor. Data analysis was by using Statistical Package for Social Sciences (SPSS version 20) and Microsoft Office Excel 2016 for Windows 7. The reliability value of the instrument was α = 0.803. Descriptive data are presented in the form of frequencies and percentages. Spearman’s Rho (rs) correlation coefficient was used for inferential statistical data to explain the relationships and influences between the variables studied. The results showed that the chemical problem solving fun item for the internal factor construct was the most dominant factor in the selection of chemistry major. There was no significant relationship between the pleasure factors of chemistry problem solving with gender, race, and academic achievement. Similarly, teachers’ teaching style (external factors) and career prospects (side factors) and awareness of the importance of chemistry subjects (internal factors) and the credibility of academic teaching staff in public universities (side factors) but have a very weak relationship. The findings of the study indicate that transformation in chemistry learning needs to be applied in 21st century learning. Attitudes and interests towards science and chemistry should be nurtured among students and the community to drive the development of the country in line with the development of the k-economy and the industry 4.0 revolution.